Abnormal monocyte differentiation and function in chronic myelomonocytic leukemia. Issue 1 (January 2022) - Dhawan, Abhishek; Padron, Eric
Abstract : Purpose of review: Monocytes serve as the phagocytic defense surveillance system of the human body. Although there is comprehensive evidence regarding monocyte development, characterization and function under steady state hematopoietic continuum, the deviations and complexities in the monocyte secretome during myeloid malignancies have not been comprehensively examined and delineated. Recent findings: This review summarizes the aspects of development, functions, transcriptional and cytokine-mediated regulation of monocytes during steady state hematopoiesis and also contrasts the aberrations observed in myelomonocytic leukemias like chronic myelomonocytic leukemia (CMML). It presents the findings from the major studies highlighting the novel markers for identifying CMML monocytes, altered signaling cascades, roles in disease progression and potential therapeutic interventions to reduce the monocyte mediated inflammatory milieu for disease amelioration. Summary: Recent findings provide rationale for the development of therapeutic strategies aimed at disrupting the leukemic initiating cells and malignant monocyte axis.